Deciphering the geochemical link between seep carbonates and enclosed pyrite: A case study from the northern South China sea. (June 2021) - Chen, Tingting; Sun, Xiaoming; Lin, Zhiyong; Lu, Yang; Fang, Yunxin; Wu, Zhongwei; Xiao, Yang; Lin, Haixin; Lin, Xiao; Ning, Youfeng; Strauss, Harald
Abstract: Sulfate-driven anaerobic oxidation of methane (SD-AOM) is an important microbial process at methane seeps, which consumes most of the methane migrating from sediments and can lead to the formation of seep carbonate and pyrite. Geochemical proxies archived in seep carbonates have been long used to uncover the nature of seepage. Recently, the sulfur isotopic composition of enclosed pyrite shows ideal prospects for targeting the seepage dynamics, but it remains challenging due to a possible decoupled precipitation of carbonate and pyrite. In order to decipher the geochemical link between seep carbonates and enclosed pyrite, multiple geochemical proxies of both carbonate (major elements, rare earth elements, δ 13 C) and pyrite (contents and δ 34 Spy ) were analyzed from two seep sites of the northern South China Sea. Multiple carbonate phases were identified via X-ray diffraction and transmission electron microscopy, including microcrystalline aragonite and botryoidal aragonite from Haima seeps, and micritic high-magnesium calcite (HMC), weakly ordered dolomite and botryoidal aragonite from site TVG11. The δ 13 C values for carbonates from both sites exhibit very light carbon isotopic signatures (from −59.2 to −35.8‰), confirming that the carbon source is mainly derived from the oxidation of biogenic methane. For pyrite enclosed in carbonates, their contents and sulfur isotopic compositions (δ 34 Spy ) reveal generally positive correlations with Mg/Ca ratios, where HMC and dolomite show higher pyrite contents and δ 34 Spy values, but microcrystalline aragonite and botryoidal aragonite display lower pyrite contents and negative δ 34 Spy values. This is consistent with our knowledge that HMC and dolomite tend to precipitate at a deeper sulfate-methane transition zone (SMTZ) where the replenishment of seawater sulfate is limited, whereas microcrystalline aragonite and botryoidal aragonite tend to form at shallow SMTZ with enhanced seawater sulfate supplement. Thus, the δ 34 S values of pore water sulfate greatly affect the resulting sulfur isotopic composition of pyrite, i.e., the higher δ 34 Spy values in HMC and dolomite are attributed to the 34 S enrichment in pore water sulfate at deeper SMTZ. This is supported by SIMS results that pyrite entrapped in botryoidal aragonite displays lower δ 34 SSIMS values than those in HMC. Our results suggest that geochemical proxies archived in both carbonate and pyrite point to the similar sedimentary environments, suggesting an intrinsic link between these two archives in our study sites. Highlights: Multiple carbonate phases were identified from the studied seep carbonates. High-magnesium calcite (HMC) and dolomite show higher pyrite contents and δ 34 Spy values comparing to aragonite. δ 34 SSIMS values in botryoidal aragonite and HMC are consistent with their bulk δ 34 Spy, excluding later diagenetic effects. The geochemical archives in seep carbonate and enclosed pyrite suggest their synchronous formation.